Visualization of Ontologies on the Semantic Web - Dudáš, Marek; Zamazal, Ondřej; Vacura, Miroslav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2013)
For ontology development, sharing and usage, availability of a suitable visualization method is essential. Much research has been done in this area, but an ideal method is still missing. One of the reasons might be that most of the available tools offer a general visualization but various use cases require specific approaches to the visualization. This master thesis gives a general overview of current visualization methods and their implementations. Both the methods and specific visualization tools are evaluated from the perspective of several possible use case categories. Special focus is given on visualization of ontology transformations. As none of the available implementations is suitable for this use case as is, an alternative approach is proposed. This approach is based on using several existing visualization implementations together and allowing switching between them using a zoom-like function. It is experimentally implemented as a Protégé plugin.
Vedoucí práce: Ondřej Zamazal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: znalostní technologie [obor dipl. práce]; diplomové práce; master's theses